2020
DOI: 10.23736/s0375-9393.20.14323-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of strong inspiratory efforts from the analysis of central venous pressure swings: a preliminary clinical study

Abstract: A copyedited and fully formatted version will be made available soon. The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Furthermore, CVP showed a good performance for measuring WOB (r 2 = 0.89) and intrathoracic pressure swings (r 2 = 0.75) when compared to Pes. Similar conclusions were reported in a recent study by Colombo et al [ 39 ]. Assuming that ΔCVP may reflect ΔPpl, ΔPes and, therefore, the strength of inspirations, the authors aimed to determine the diagnostic accuracy of ΔCVP for strong inspiratory efforts (arbitrarily defined as ΔPes >8 mmHg).…”
Section: Clinical Studiessupporting
confidence: 93%
“…Furthermore, CVP showed a good performance for measuring WOB (r 2 = 0.89) and intrathoracic pressure swings (r 2 = 0.75) when compared to Pes. Similar conclusions were reported in a recent study by Colombo et al [ 39 ]. Assuming that ΔCVP may reflect ΔPpl, ΔPes and, therefore, the strength of inspirations, the authors aimed to determine the diagnostic accuracy of ΔCVP for strong inspiratory efforts (arbitrarily defined as ΔPes >8 mmHg).…”
Section: Clinical Studiessupporting
confidence: 93%
“…Invasive mechanical ventilation with individually tailored tidal volume and airway pressure can be the safest option for patients with severe respiratory distress Underestimating the risks of spontaneous breathing in patients assisted by a ventilator Recognizing and mitigating vigorous inspiratory efforts and frequent asynchronies can be extremely difficult. In case of doubt, esophageal pressure swings [ 4 ] (or central venous pressure swings as a surrogate [ 15 ]) should be measured, and controlled ventilation started or resumed Herein we list some mistakes we made and some lessons we learned during the first waves of the pandemic. The way we treat patients with COVID-19 has changed accordingly.…”
Section: Iatrogenic Proceduresmentioning
confidence: 99%
“…In a recent editorial regarding respiratory treatment of COVID-19, in the absence of an esophageal catheter, the use of the swings of CVP as a surrogate measure for the work of breathing was recommended [25]. Although ΔCVP was correlated with ΔPes in previous studies [11,13], many studies have shown that ΔCVP did not usually reflect the exact value of ΔPes [10,12,[14][15][16][17][18]. Lung volume, chest wall elastance, chest wall distortion, and volume status including CVP and air trapping may affect the relationships between ΔPpl, ΔPes, and ΔCVP [12,21,[26][27][28][29].…”
Section: Plos Onementioning
confidence: 99%
“…Lung volume, chest wall elastance, chest wall distortion, and volume status including CVP and air trapping may affect the relationships between ΔPpl, ΔPes, and ΔCVP [12,21,[26][27][28][29]. As a result, the reported values of ΔPes/ΔCVP were not consistent and, more importantly, varied widely among individuals [10][11][12][13][14][15][16][17]. To overcome this problem, we used the ratio of ΔPpl to ΔCVP during an occlusion test to correct the raw ΔCVP values and estimate ΔPpl more accurately than when simply using ΔCVP.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation